Analisis Gangguan Pada Sistem Gardu Listrik Berbasis Gas Insulated Switchgear 150 kV Dengan Metode High Voltage Test - Bachri, Karel Octavianus; Jonathan, Edoardo; Soewono, Arka Dwinanda (Cylinder : Jurnal Ilmiah Teknik Mesin, 2023)
The insulator system in substations is essential in maintaining safety and efficiency in electricity transmission and distribution lines. The purpose of this research is to conduct High Voltage tests to check possible malfunctions in a gas-insulated switchgear (GIS) in a 150 kV substation following IEC standard 62271-203. Insulation Resistance (IR) measurement results for components in the GIS system show that the system still has high insulation resistance for the R, S, and T phases. High voltage testing results for the three-phase Gas Insulated Switchgear also did not exhibit current leakage, meaning the system still operates satisfactorily.